Rasionalitas Penggunaan Antibiotik Terhadap Pengobatan Demam Tifoid Anak Di RSUD Cut Meutia Aceh Utara 2022 - Yuziani Yuziani; Adri Adri; Mardiati Mardiati (Majalah Kedokteran Indonesia, 2024)
Introduction: Typhoid fever is a systemic disease caused by bacterial infection, so rational use of antibiotics is important in the treatment of typhoid fever to support effectiveness and prevent antibiotic resistance. The aim of this study was to assess the rationality of antibiotic use in pediatric typhoid fever patients at the Cut Meutia Regional General Hospital, North Aceh using the Gyssens method based on IDAI and Ministry of Health guidelines.Method: This research is descriptive. Samples were taken using purposive sampling technique and time limited sampling method. The samples in this study were medical records of pediatric typhoid fever patients in the inpatient room of Cut Meutia Hospital, North Aceh 2022.Results: The results obtained ceftriaxone as the most commonly administered antibiotic, followed by cefixime, and quinolones. For rationality, there was ceftriaxone classified as category 0 as much as 4,4%, Category II A in ceftriaxone and cefixime as much as 17,5%, category II B in ceftriaxone as much as 0,6%, category III B in ceftriaxone and cefixime as much as 51,2%, category IV B in quinolones as much as 6,9%, and category VI in incomplete medical records as much as 19,4%.Conclusion: The conclusion of this study is that the most frequently used antibiotic is ceftriaxone, while the level of rationality indicates a significant proportion of irrational use.